Back to nowhere - Fundakubi, Zukile Anthony (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2017)
My writing contains elements of hard-boiled detective fiction and crime writing. My stories, written in isiXhosa and English and a mixture of both, transplant these genres into a South African township setting where gang violence dominates and life is cheap. They are driven by uniquely South African characters, brutal crime scenes and fear-inspiring suspense, but none the less still full of humour. I want my work to entertain the reader while also looking realistically and critically at the problem of crime in our townships. I draw on influences of African and Latin American writers to create South African crime fiction in a realistic urban setting, with dynamic characters and sharp dialogue.,Le ngqokelela yamabali iqulathe amabali angobomi babantu abasezilokishini nabo bahlala ezilalini. Nangona umfundi angahle awafumanisa ehlekisa amanye elusizi, injongo yombhali asikukuhlekisa nakunyanzelisa imfundiso koko ikuzoba ubomi bababantu, bephila kwezi ndawo neengxaki abajongene nazo. Imeko yaba bantu kumakhaya ngamakhaya yiyo ebangele ukuba umbhali abelane nomfundi ngokuqhubekayo ebomini.,This thesis is presented in two parts: English and isiXhosa
Ntakana ntyilo-ntyilo
Keywords: Creative writing (Higher education) -- South Africa; South African fiction (English) 21st century; Short stories, South African (English) 21st century; Xhosa fiction 21st century; Short stories, Xhosa 21st century; Detective and mystery stories 21st century